2016
DOI: 10.1186/s40560-016-0163-2
|View full text |Cite
|
Sign up to set email alerts
|

Renal replacement therapy neutralizes elevated MIF levels in septic shock

Abstract: BackgroundMacrophage migration inhibitory factor (MIF) is known to amplify the immune response in septic animal models. Few clinical data support this pro-inflammatory role in septic patients. Renal replacement therapy (RRT) as adjuvants in the complex therapy of sepsis has been proposed as a possible approach to eliminate elevated circulating cytokines. Since recent data suggest that MIF can be effectively removed from the circulating blood pool in patients with chronic kidney disease, we here aimed to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…As techniques improve, blood purification methods, including continuous renal replacement therapy (CRRT) and hemoperfusion (HP), are becoming more commonly used as treatment methods for sepsis ( 8 , 9 ). Previous reports have suggested that the attenuation of several pro-inflammatory cytokines, such as interleukins and tumor necrosis factors, may be the primary underlying mechanism of blood purification as an effective treatment for sepsis ( 10 , 11 ). However, other studies have reported no association between the attenuation of cytokines and the use of blood purification techniques during sepsis ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…As techniques improve, blood purification methods, including continuous renal replacement therapy (CRRT) and hemoperfusion (HP), are becoming more commonly used as treatment methods for sepsis ( 8 , 9 ). Previous reports have suggested that the attenuation of several pro-inflammatory cytokines, such as interleukins and tumor necrosis factors, may be the primary underlying mechanism of blood purification as an effective treatment for sepsis ( 10 , 11 ). However, other studies have reported no association between the attenuation of cytokines and the use of blood purification techniques during sepsis ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cutoff value of standard CRRT is 30–40 kDa [21], and the molecular weight of common cytokines such as interleukin (IL) 1 beta is 17 kDa, IL-1RA is 15–20 kDa, IL-2 is 15 kDa, IL-6 is 26 kDa, IL-8 is 8 kDa, macrophage migration inhibitory factor (MIF) is 12.5 kDa, IL-10 is 35–40 kDa and tumor necrosis factor (TNF) α is 51kDa. So among the most included cytokines, only IL-10 and TNF-α are outside the cutoff value of standard CRRT; all other cytokines can be slowly removed in standard CRRT [21, 23-25]. However, certain clinical research declared that the concentration of plasma cytokines makes no difference during CRRT, though some cytokines can be detected in the filtrate fluid [24].…”
Section: The Role Of Crrt In Inflammation and Metabolic Adaptation Inmentioning
confidence: 99%
“…It has been proved that decreased MIF concentration in cancer can induce macrophage polarization from proinflammatory macrophages (predominantly CD11b + /Ly6C high cells) to pro-wound healing macrophages (CD11b + /Ly6C intermediate cells) [33]. The MIF level decreases obviously during CRRT or hemodialysis and can improve the prognosis [23, 34]; however, how it works is still unknown and the MIF plasma pool is reconstituted early after the termination of hemodialysis from unknown sources. Probably the same thing happens during CRRT of septic AKI patients.…”
Section: The Role Of Crrt In Inflammation and Metabolic Adaptation Inmentioning
confidence: 99%
“…This is important, as acute kidney injury is a systemic disease affecting inflammation and function of different organs (16). Against this background it can be speculated that early treatment attenuates pro-inflammatory effects and a further decline in other organs function (17). Patients assigned to the early group in the AKIKI trial are almost identical with, but at least very similar to the patients assigned to the late group in the ELAIN trial.…”
mentioning
confidence: 98%